Lithuania’s Citizens’ Employment Development Towards Integrating Eu Period - Martinkus, Bronislovas (Ekonomika, 2002)
The article analyzes Lithuania’s citizens employment development toward integrating EU. The article presents employment statistic data analysis, unemployment reasons, and the decisions for unemployment decrease. The article analyzes employment influence on labor market during integration to EU process. Basing OD the research data, scientific research data conclusions about employment increasing presented.